2014
DOI: 10.1016/j.pain.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of missing data and methods used to accommodate them in recent analgesic clinical trials: ACTTION systematic review and recommendations

Abstract: Missing data in clinical trials can bias estimates of treatment effects. Statisticians and government agencies recommend making every effort to minimize missing data. Although statistical methods are available to accommodate missing data, their validity depends on often untestable assumptions about why the data are missing. The objective of this study was to assess the frequency with which randomized clinical trials published in 3 major pain journals (ie, European Journal of Pain, Journal of Pain, and Pain) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Multilevel linear growth modeling was uniquely suitable for the present study, as it permits (a) the responses to treatment to vary heterogeneously both over time and between individual patients, (b) the number of assessments and time between assessments to be distinct for each individual, and (c) accurate estimation in the presence of missing data (13)(14)(15). Changes in efficacy endpoints in response to cryoablation were analyzed using a 2-level model (level 1: visit; level 2: patient) with the variable for visit (baseline/day 0, day 7, day 45, long-term follow-up) included both as a fixed effect and as a random effect at the patient level.…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel linear growth modeling was uniquely suitable for the present study, as it permits (a) the responses to treatment to vary heterogeneously both over time and between individual patients, (b) the number of assessments and time between assessments to be distinct for each individual, and (c) accurate estimation in the presence of missing data (13)(14)(15). Changes in efficacy endpoints in response to cryoablation were analyzed using a 2-level model (level 1: visit; level 2: patient) with the variable for visit (baseline/day 0, day 7, day 45, long-term follow-up) included both as a fixed effect and as a random effect at the patient level.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent method reported was a complete case analysis (that is, including only participants who provided all necessary outcome data), which assumes that the data are missing completely at random (that is, missingness is unrelated to observed or unobserved outcomes), an assumption that is unlikely to be accurate because participant withdrawals in pain clinical trials are often due to AEs or lack of effectiveness. 34 Other than 1 article in which the authors used a 2-way mixed analysis of variance model to accommodate missing data, no authors of published articles reported methods currently recommended by statisticians, such as multiple imputation, linear mixed models (for example, mixed-effect model repeated measure), or weighted generalized estimating equations. [9][10][11] In addition, none of the authors in any of the articles reported multiple methods to accommodate missing data to evaluate the sensitivity of the results to the assumptions made about the pattern of missing data (that is, sensitivity analysis).…”
Section: Discussionmentioning
confidence: 99%
“…We adapted a coding manual (Appendix 2; available online at the end of this article) from previous methods of Gewandter and colleagues 33,34 and Smith and colleagues 39 to evaluate reporting of details that can affect accuracy of treatment effect estimates (for example, identification of primary analyses, methods to adjust for multiple primary analyses, and methods to accommodate missing data), as well as fulfillment of the 10 CONSORT harms reporting recommendations. 25 We coded the method to accommodate missing data as unsure if the reported statistical test accommodates missing data only when certain statistical packages are used in specific ways, but insufficient information was provided about what was implemented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IMMPACT was conceptualized as a series of meetings involving industry, academia and the FDA to "develop consensus reviews and recommendations for improving the design, execution and interpretation of clinical trials for pain" (IMMPACT, 2002). IMMPACT has published recommendations on patient-reported outcomes (Turk et al, 2006), assay sensitivity (Dworkin et al, 2012), abuse-deterrence (Dworkin et al, 2012), multiple endpoints and missing data analysis (Turk et al, 2008a;Gewandter et al, 2014b), disclosure of authorship contributions (Hunsinger et al, 2014) and interpretive "spin" (Gewandter et al, 2015). Together, these articles argue for the necessity of widely agreedupon standard forms of recording and reporting data from clinical trials, as well as on alternative design strategies such as enrichment.…”
Section: Immpact and Acttion: Streamlining And Standardizing The Painmentioning
confidence: 99%